Archaic Adaptive Introgression in TBX15/WARS2. (22nd December 2016) - Racimo, Fernando; Gokhman, David; Fumagalli, Matteo; Ko, Amy; Hansen, Torben; Moltke, Ida; Albrechtsen, Anders; Carmel, Liran; Huerta-Sánchez, Emilia; Nielsen, Rasmus
Abstract : A recent study conducted the first genome-wide scan for selection in Inuit from Greenland using single nucleotide polymorphism chip data. Here, we report that selection in the region with the second most extreme signal of positive selection in Greenlandic Inuit favored a deeply divergent haplotype that is closely related to the sequence in the Denisovan genome, and was likely introgressed from an archaic population. The region contains two genes, WARS2 and TBX15, and has previously been associated with adipose tissue differentiation and body-fat distribution in humans. We show that the adaptively introgressed allele has been under selection in a much larger geographic region than just Greenland. Furthermore, it is associated with changes in expression of WARS2 and TBX15 in multiple tissues including the adrenal gland and subcutaneous adipose tissue, and with regional DNA methylation changes in TBX15 .